Influência da espessura do espaçador e da estratégia de fresagem na adaptação e na carga de fratura de coroas cerâmicas confeccionadas em CAD/CAM - Schelbauer, Ricardo Susin (2021)
The objective of this study was to evaluate the influence of the internal spacer thickness (70, 110 and 150 μm) and the milling strategy (normal/conventional mode and veneer mode) on marginal and internal fit and load bearing capacity of CAD/CAM feldspathic ceramic crowns. From a master model, 60 composite resin dies were obtained, each was individually scanned and feldspathic ceramic crowns (CEREC Blocs) were fabricated using a CAD/CAM system. The marginal and internal adaptation was evaluated by micro-CT images, with InVesalius software, in sagittal and axial planes. After the luting with self-adhesive cement and storage for 7 days, the specimens were submitted to the fracture load test. The marginal and internal adaptation and fracture load data were analyzed by two-way ANOVA Tukey’s test (α=5%). For marginal fit, there was no difference between the milling strategies and the different internal spacers. As for internal fit, statistically significant differences were observed in the sagittal plane (at the axial wall and axio-occlusal angle) and axial plane (at the lingual, linguo-distal, buccal and buccal-mesial walls) only for the internal spacer factor. Greater gaps were observed in crowns with internal spacer of 150 μm compared to 70 μm. For fracture load, there were no significant differences for milling strategy and internal spacer. Fracture load ranged from 924.2 N and 1297.2 N. It can be concluded that the internal spacer and milling strategy did not influence the resistance to the CAD/CAM feldspathic ceramic crowns. However, in both milling strategies, higher marginal and internal fit was found when using the 150 μm spacer.